Stearic Acid Modified Stearyl Alcohol Oleogel: Analysis of the Thermal, Mechanical and Drug Release Properties. Issue 4 (27th May 2017) - Yadav, Indu; Kasiviswanathan, Uvanesh; Soni, Chandan; Paul, Suprio R.; Nayak, Suraj K.; Sagiri, Sai S.; Anis, Arfat; Pal, Kunal
Abstract: The present study delineates the effect of stearic acid on the properties of stearyl alcohol oleogel. Herein, a series of oleogels were prepared by mixing different proportions of fatty alcohol (Stearyl alcohol; gelator) and fatty acid (stearic acid; co‐gelator). The characterization of the oleogels was done by thermal, macro‐scale stress relaxation, drug release, and antimicrobial studies. The oleogels were formed by the self‐assembly of stearyl alcohol/stearic acid. Thermal studies indicated that the stearic acid alters the crystal morphology, polymorphic transition and rate of crystallization of stearyl alcohol. The firmness of the oleogels with higher stearic proportion was better, which was due to the formation of a rigid network structure of stearyl alcohol in the presence of stearic acid. The release of ciprofloxacin hydrochloride, model drug, from the oleogels was better from the oleogels with higher stearic acid content. The release of the drug from the oleogels was Fickian diffusion‐mediated; except the oleogel with the highest stearic acid proportion. The antimicrobial study showed that the drug loaded oleogels were able to resist the growth of Escherichia coli, model microbe.